Online security in e-government as an antecedent of cost-effectiveness and quality in business operations (2023)
The Colombian Government launched an e-government initiative in 2008 to facilitate communication among the government, citizens and organizations. Considering the high level of mistrust of citizens and businesses toward governmental institutions, the government must ensure the security of the information handled and provided by online users. Results to date have not been adequate in the usage of e-government systems. The purpose of this study is to evaluate whether the level of online security affects usage and impacts the cost-effectiveness and quality of the operations and, consequently, the operational effectiveness of organizations using e-government systems.